Pemanfaatan Aplikasi Tiktok sebagai Media Dakwah di UIN Fatmawati Kota Bengkulu - Yuni Rahayu, Puspa; Ermanti Lubis, Riyani; Junia Restika, Anggi; Septriani, Tesa; Zubaidah, Zubaidah (DAWUH : Islamic Communication Journal, 2022)
Tiktok app has many users from all walks of life because of its simple yet complete look. Their Tiktok feeds create interesting content and can receive a direct response from all their followers. Da'i are also asked to creatively package the da'wah message so that it reaches the mad'u in a relaxed and fun way. Islamic preachers, like many Tiktok users, use this platform well to spread their teachings in this day and age. Tiktok is currently turning into a medium for spreading da'wah, the purpose of using the Tiktok application as a da'wah media is to make it easier to convey information to all people and especially among young people today with the Tiktok application, important messages will be easily conveyed to the public. Of course, TikTok can also arouse the religious spirit of the community with da'i presenting inspirational and uplifting da'wah. This research is descriptive qualitative research and uses an inductive approach analysis. The informant identification technique uses purposive sampling, namely the selection of samples based on certain considerations. Based on the research results, it can be concluded that the Tiktok application has significant benefits in disseminating information to mad'u.